Serum connective tissue markers as predictors of advanced fibrosis in patients with chronic hepatitis B and D - Gülseren Seven; Senem Ceren Karataylı; S.Kenan KÖSE; Mustafa YAKUT; Gökhan KABAÇAM; Murat TÖRÜNER; Aylin OKÇU HEPER; Michael VOELKER; Esra ERDEN; A. Mithat Bozdayı; Özden UZUNALİMOĞLU 0; Hakan BOZKAYA; et al. (Turkish Journal of Gastroenterology, 2019)
-